The reign of the phallus : sexual politics in ancient Athens - Keuls, Eva C. (University of California Press, 1993)
At once daring and authoritative, this book offers a profusely illustrated history of sexual politics in ancient Athens. The phallus was pictured everywhere in ancient Athens: painted on vases, sculpted in marble, held aloft in gigantic form in public processions, and shown in stage comedies. This obsession with the phallus dominated almost every aspect of public life, influencing law, myth, and customs, affecting family life, the status of women, even foreign policy. This is the first book to draw together all the elements that made up the "reign of the phallus"--Men's blatant claim to general dominance, the myths of rape and conquest of women, and the reduction of sex to a game of dominance and submission, both of women by men and of men by men. In her elegant and lucid text Eva Keuls not only examines the ideology and practices that underlay the reign of the phallus, but also uncovers an intense counter-movement--the earliest expressions of feminism and antimilitarism. -- Publisher description